The subconscious idea - Holderman, Pearl C. (My University, 1903)
Introduction: Pope has said, “that the proper study of mankind is man”. It is certain that the highest and most important study of man is mind. From the beginning of learning, philosophy has speculated on the mind or soul of man, its attributes, its processes, and its relation to the physical organism. Science, philosophy and theology have set forth man’s trinity. Plato’s idea of terrestrial man was that he is a trinity, made up of “soul, soul-body, and earth-body”. Socrates believed that he was at times directed by a spirit independent of himself. The “salt, sulphur and mercury,” of the ancient alchemists doubtless referred to the same idea. Many experiences might be related which have had their origin within man, yet which have seemed to come from exterior sources and being outside the commonly recognized power of the human mind have been attributed to the supernatural. There has been an operative force, an intelligent force in man which he has denied being a part of himself—a force sometimes manifesting itself in harmony with, but at times in opposition to, his will and desire.
Citation: Holderman, Pearl C. The subconscious idea. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Philosophy; Study of Mankind; Mind; Soul; Theses; Manuscripts (documents)